UPAYA GURU DALAM MENUMBUHKAN KEMAMPUAN MEMBACA GAMBAR DI KELOMPOK A RA IBNU HAJAR MUHARTO MALANG - Emi Kristiana; Mohammad Afifulloh; Ika Anggraheni (UNISMA, 2020)
In learning at an early age reading is very important, because reading is a way for children to be able to understand and understand about language and reading through the symbols they learn, by reading images with existing symbols in accordance with the way they read. Based on the problems faced in Raudhatul Athfal Ibnu Hajar Malang namely the lack of collaboration between parents and teachers, this is one of the obstacles faced by teachers in learning in schools for children, especially in learning to read pictures, then there must be good cooperation between teachers, parents and children. In order to get the success obtained by all parties. The purpose of this research is to find out how to read pictures, To find out how the teacher's efforts in growing the ability to read images, To find out what obstacles faced by teachers in growing the ability to read pictures in Raudhatul Ibnu Hajar Muharto Malang. Researchers conducted research with descriptive qualitative methods. collecting data and information obtained by researchers using the method of observation, interviews and documentation. The results showed that the teacher had succeeded in learning to grow the ability to read pictures in Raudhatul Athfal Ibnu Hajar Malang City, this can be seen from the observation that of 22 children there are 4 children who are less able to read pictures, if viewed from here can it was concluded that most of the children were able to read pictur using symbols. The activities in this learning, which are carried out by the teacher, are using a picture card media that is very interesting for the child so that it is very easy for the child to memorize symbols more quickly and the child can more quickly read the cards properly. The principal's advice is that teachers continue to increase their creativity by using existing media and by getting information from outside the school, by means of teachers participating in various kinds of training, workshops, learning in electronic media, seminars and other activities that seek to improve the progress and quality of the school in the eyes of the community around the school, especially for all parents of all students.